The spectrum of neutralizing and non-neutralizing anti-FVIII antibodies in a nationwide cohort of 788 persons with hemophilia A - Oomen, Ilja; Verhagen, Marieke; Miranda, Mariarosaria; Allacher, Peter; Beckers, Erik A. M.; Blijlevens, Nicole M. A.; Bom, Johanna G. van der; Coppens, Michiel; Driessens, Mariëtte; Eikenboom, Jeroen C. J.; Fijnvandraat, Karin; Hassan, Shermarke; et al. (Frontiers in Immunology, 2024)
Objectives: Anti-factor VIII (FVIII) antibodies have been reported to exhibit both neutralizing as well as non-neutralizing characteristics. This is the first study investigating the full spectrum of FVIIIspecific antibodies including non-neutralizing antibodies, very-low titer inhibitors and inhibitors in a large nationwide population of persons with hemophilia A of all severities. Methods: All persons with hemophilia A (mild (FVIII >5-40 IU/dL)/moderate (FVIII 1-5 IU/dL)/severe (FVIII <1 IU/dL)) with an available plasma sample, who participated in the sixth Hemophilia in the Netherlands study between 2018 and 2019, were included. Presence of anti-FVIII antibodies of the immunoglobulin A, M, and G isotype, and IgG subclasses, along with antibody titer levels were assessed using direct-binding ELISAs. FVIII-specificity was assessed using a competition-based ELISA approach. The inhibitor status was determined using the Nijmegen ultra-sensitive Bethesda assay (NusBA) and Nijmegen Bethesda assay (NBA). Results: In total, 788 persons with hemophilia A (336 (42.6%) mild, 123 (15.6%) moderate, 329 (41.8%) severe hemophilia) were included. The median age was 45 years (IQR 24-60), and the majority (50.9%) had over 150 exposure days to FVIII concentrates. Within our population, 144 (18.3%) individuals had non-neutralizing FVIII-specific antibodies, 10 (1.3%) had very low-titer inhibitors (NusBA positive; NBA negative), and 13 (1.6%) had inhibitors (both NusBA and NBA positive). IgG1 was the most abundant FVIII-specific antibody subclass and highest titer levels were found for IgG4. In individuals without a reported history of inhibitor development, no clear differences were observed in antibody patterns between those who were minimally or highly exposed to FVIII concentrates. IgG4 subclass antibodies were only observed in persons with a reported history of FVIII inhibitor, or in those with a currently detected (very-low titer) inhibitor.In this cross-sectional study, we identified non-neutralizing antibodies in a relatively large proportion of persons with hemophilia A. In contrast, in our population, consisting of persons highly exposed to FVIII concentrates, (very low-titer) inhibitors were detected only in a small proportion of persons, reflecting a well tolerized population. Hence, our findings suggest that only a small subpopulation of non-neutralizing FVIII-specific antibodies is associated with clinically relevant inhibitors.